An Afghan Diary. The Year 2002 - Mikhail Konarovsky (Международная аналитика)
In late 2001 Russia supported the International anti terrorist coalition’s activity aimed at toppling Al Qaida being backed by the Taliban regime. The Interim Administration of Afghanistan based on decisions of the Bonn international conference, had been formed. Simultaneously, the Embassy resumed its activity and a new Ambassador had been confirmed by the International Committees of both Chambers of the Federal Assembly. At the meeting in Kremlin President Putin outlined urgent priorities of Russia’s policy in Afghanistan aimed at reestablishing and strengthening of ties with that nation at the new, post Taliban stage of its history. Besides urgent political issues, launching of Embassy’ s everyday administrative and life activity let alone the recovery of the Embassy’s compound, were among the priorities, with destroyed national infrastructure as well as economy in Kabul and all over the country.